PENGGUNAAN METODE TOTAL PHYSICAL RESPONSE DALAM MENINGKATKAN KEMAMPUAN VOCABULARY SISWA PADA MATA PELAJARAN BAHASA INGGRIS KELAS V DI SEKOLAH DASAR NEGERI 2 NALU - Dinah Abidah; Theopilus C. Motoh (Program Studi Teknologi Pendidikan Universitas Madako Tolitoli, 2025)
This study aims to improve students' Vocabulary skills using the Total Physical Response (TPR) method. The type of research is Classroom Action Research. There are 17 students in class V (A) SDN 2 Nalu who are studied. The research instruments used are teacher and student observation sheets, and test sheets using Wordwall Learning Media. The results of the study showed that in cycle I which obtained a score of 53% from 17 students, only 8 students completed and 9 students had not completed. Meanwhile, in cycle II students' Vocabulary skills increased with a score of 88% from 17 students, there were 15 students who completed and 2 students had not completed. Cycle II was stopped because students had achieved 88% classical completion. The number of students in one class was 17 people and individually students achieved KKM 70. From these data it can be concluded that learning was declared complete individually and classically. So, the use of the TPR method can improve students' vocabulary